SnRK1 and TOR: modulators of growth-defense trade-offs in plant stress responses. - Margalha, Leonor (2020)
The evolutionarily conserved protein kinase complexes SnRK1 and TOR are central metabolic regulators essential for plant growth, development, and stress responses. They are activated by opposite signals, and the outcome of their activation is, in global terms, antagonistic. Similarly to their yeast and animal counterparts, SnRK1 is activated by the energy deficit often associated with stress to restore homeostasis, while TOR is activated in nutrient-rich conditions to promote growth. Recent evidence suggests that SnRK1 represses TOR in plants, revealing evolutionary conservation also in their crosstalk. Given their importance for integrating environmental information into growth and developmental programs, these signaling pathways hold great promise for reducing the growth penalties caused by stress. Here we review the literature connecting SnRK1 and TOR to plant stress responses. Although SnRK1 and TOR emerge mostly as positive regulators of defense and growth, respectively, the outcome of their activities in plant growth and performance is not always straightforward. Manipulation of both pathways under similar experimental setups, as well as further biochemical and genetic analyses of their molecular and functional interaction, is essential to fully understand the mechanisms through which these two metabolic pathways contribute to stress responses, growth, and development.